1991
DOI: 10.1021/jm00109a025
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel series of (2-quinolinylmethoxy)phenyl-containing compounds as high-affinity leukotriene D4 receptor antagonists. 4. Addition of chromone moiety enhances leukotriene D4 receptor binding affinity

Abstract: The combination of the benzopyran-4-one ring, a moiety found in the prototype leukotriene antagonist, FPL 55,712, with the (2-quinolinylmethoxy)phenyl group led to a significant increase in leukotriene receptor binding affinity. This modification resulted in a 10,000-fold improvement in binding affinity compared to FPL 55,712. Compound 7 (RG 12553), with a Ki value of 0.1 nM, has higher affinity than the natural agonist LTD4 and is one of the most potent LTD4 antagonists reported. The structure-activity relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Zhang et al (1995) reported that the chromone moiety effectively inhibits a LTD4-induced increase in vascular permeability. Huang et al (1991) found that the chromone moiety in the benzopyran-4-one ring led to a significant increase in leukotriene D4 receptor binding affinity. Sener et al (2005) also reported that treatment with a leukotriene receptor antagonist prevented gastrointestinal damage as well as the changes in biochemical parameters in all of the tissues investigated in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (1995) reported that the chromone moiety effectively inhibits a LTD4-induced increase in vascular permeability. Huang et al (1991) found that the chromone moiety in the benzopyran-4-one ring led to a significant increase in leukotriene D4 receptor binding affinity. Sener et al (2005) also reported that treatment with a leukotriene receptor antagonist prevented gastrointestinal damage as well as the changes in biochemical parameters in all of the tissues investigated in their study.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1980s and 1990s the discovery and development of novel LT receptor inhibitors based on the chromone nucleus prompted the emergence of pranlukast ( described as LTD4 antagonist [156] (Fig. 2.21).…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…[38] Combinationo ft he chromone moiety with the (quinolin-2ylmethoxy)phenyl group led to the discovery of the most potent LT receptora ntagonistr eported so far,R G12553 (21; Figure 11), whichh as even highera ffinity than the natural ligand LTD4 (18;F igure 10). [39] Through SAR studies it was possible to verify that the presence of the chromone moiety itself is not sufficient for high bindinga ffinity.F urthermore,s tructural features like the tetrazole group can be regarded as an acidic function that improves receptor affinity.…”
Section: Lipoxygenase Inhibitorsmentioning
confidence: 99%